The Not Quite Innocent Bystander: Writings of Edward Steuermann - Steuermann, Edward; Steuermann, Clara; Porter, David; Schuller, Gunther; Cantwell, Richard; Messner, Charles (Lincoln University of Nebraska Press, 1989)
Steuermann was hardly a bystander. A pupil of composer Schoenberg and a noted teacher and performer, he was an active participant as well as acute observer and incisive critic of the new music scene between 1910 and 1964. This is an uneven collection of writings, several of them incomplete jottings, some witty, others complex to the point of obscurity, many quite profound and informative. Steuermann deals with issues as diverse as serial composition and stage fright. An interesting insight into the often private thoughts of a talented and observant artist.
Keywords: Historically informed performance; Music criticism